Studying the biological activity of Salicylic acid and the glycoalkaloids extract on the metabolism of both proteins and carbohydrates in Zea mays L. mesocotyl (Damascus University Journal for the basic sciences, 2021)
The effect of some familiar growth regulators such as salicylic acid and Indole acetic acid, and the effect of extract of steroidal glycoalkaloids obtained from the surface layer of potato tubers had been studied on the metabolism of proteins and carbohydrates within the cells of Zea mays mesocotys (Ghouta 82) which were grown for 6 days in the dark and in good ventilation conditions. Salicylic acid was deployed at 50 mg/l and steroidal extract with concentrations 50, 100 and 200 mg/l. the results compared with the initial state of water.Data were showed that steroidal extract and Salicylic acid significantly increased the concentration of hexose, pentose and pentozanes, but there was no important effects on starch and structural carbohydrates. On the other hand, the Indole acetic acid increased the concentration of hexose and pentozanes. Only the studied compounds and steroidal extract at concentration 100 mg/l increased the concentration of total proteins and the percentage of growth of zea maize kernels compared with the initial state of water.
Keywords: : growth regulators; zea mays (Ghouta 82); carbohydrates; proteins; glycoalkaloids